Early Triassic beetle fauna (Insecta: Coleoptera) from the Eastern Siberian locality Alisa quarry showing late Permian taxa composition - Yan, Evgeny V.; Felker, Anastasia S.; Strelnikova, Olesya D. (Zootaxa, 2025)
From the Lowermost Triassic locality Alisa quarry (Krasnoyarsk Territory, Tura village vicinity, Nidym Formation, Lower Triassic) insect-bearing strata of a yellowish-grey tuffaceous siltstone was located 0.5 m below the basalt flow that demarcates the Permian-Triassic border. Sixteen beetle specimens: five belonging to three Permocupedidae (Permocupedinae) species, Archicupes storozhenkoi sp. nov., Cytocupes magnus sp. nov., Tatarocupes brevicellularis sp. nov.; one specimen belongs to new monotypic Asiocoleidae genus, Alisacupes dunaevi gen. et sp. nov. Ten specimens were distributed between two Schizocoleidae genera: Uskatocoleus Rohdendorf 1961, U. turensis sp. nov. and three species of Schizocoleus Rohdendorf 1961: S. frumentum sp. nov., S. maximus sp. nov. and S. subtilis sp. nov. Coleoptera composition in Alisa quarry locality is typical for the end Permian, showing no signs of rapid evolutionary changes at the Permian-Triassic boundary. In addition to insects, the Alisa quarry yielded abundant fern and conifer fossils, along with occasional fish scales and conchostracan shells. The site represents a paleoenvironment of shallow, ephemeral freshwater pools.